2011
DOI: 10.1117/12.880382
|View full text |Cite
|
Sign up to set email alerts
|

100W 1st generation laser-produced plasma light source system for HVM EUV lithography

Abstract: We reported 1st generation Laser-Produced Plasma source system "ETS" device for EUV lithography one year ago 1) . In this paper we update performance status of the 1st generation system. We have improved the system further, maximum burst power is 104W (100kHz, 1 mJ EUV power @ intermediate focus), laser-EUV conversion efficiency is 2.5%. Also continuous operation time is so far up to 8 hours with 5% duty cycle is achieved. We have investigated EUV plasma creation scheme by small experimental device which is fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Experimental results given in Ref. 1 for the same droplet diameter as in our study showed 2.3% CE "with a pre-pulse irradiation" and 3.25% CE "with improved pre-pulse irradiation". We obtained in our simulations 3% CE that is close to the above data.…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…Experimental results given in Ref. 1 for the same droplet diameter as in our study showed 2.3% CE "with a pre-pulse irradiation" and 3.25% CE "with improved pre-pulse irradiation". We obtained in our simulations 3% CE that is close to the above data.…”
Section: Introductionmentioning
confidence: 50%
“…8,9 The second one is related to utilizing the evaporated and fragmented parts of the droplet. 1 Heating of this matter is reasonable after delay in the ls range, since velocities of this components is 10-100 times lower than plasma velocity 10 and spatial expansion of such matter to areas covered by the larger plasma spot requires longer time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although availability of a reliable high power source [2][3][4] is arguably the most daunting of these challenges, several mask issues are also of major concern. The most pressing and well known of these issues is mask defectivity [5].…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 -Sn-LPP EUV light source is deemed to be the most promising solution, as the 13.5 nm wavelength high power (>200 W) light source for high volume manufacturing (HVM) EUV lithography (EUVL) [1][2][3][4], because of the high efficiency, power scalability, and spatial freedom around plasma. Therefore, we have chosen the LPP-EUV method.…”
Section: Introductionmentioning
confidence: 99%